A modified Weibull model for design of oscillated high hydrostatic pressure processes. (May 2021) - Zhu, Si; Li, Bing; Chen, Guibing
Abstract: During high hydrostatic pressure (HHP) processing, pressure can be applied in a single cycle of pressurization, pressure holding, and depressurization or multiple cycles. The latter is called oscillated HHP (OHHP) processing. In this study, it was hypothesized that the pressure gradient during HHP processing is positively related to the lethal rate, based on which a modified Weibull model was developed to describe the microbial inactivation rate as a function of pressure and pressure gradient. The model provided good fits to published survival data of Salmonella Enteritidis, Escherichia coli, and Listeria innocua, as indicated by small RMSE values being less than 0.33 log. Using the obtained parameters, the model showed good performance in predicting microbial survival ratios in independent tests, the absolute errors being less than 0.27 log, and both accuracy and bias factors being fairly close to 1. Based on the developed model, the pressurization rate must be higher than a critical value to make an OHHP process more efficient than a single-cycled one, and an optimal OHHP process should involve the highest pressurization and depressurization rates and no pressure holding time. Finally, a web-based software tool was developed to implement the modified Weibull model for design of OHHP processes. Highlights: The pressure gradient in a HHP process is positively related to the lethal rate. An effective oscillated HHP process must exceed a critical pressurization rate. An optimal oscillated HHP process has no pressure holding time. A web-based software tool was developed to implement the developed model.